Analisis Nilai Manfaat Jasa Lingkungan Air Melalui Pembayaran Jasa Lingkungan Pada Hutan Desa Dusun Lubuk Beringin Kabupaten Bungo - Irfan Adhi Hidayat Ismail; Hamzah Hamzah; Muhamad Syafri (Jurnal Pembangunan Berkelanjutan, 2022)
Environmental services are activities to utilize the potential of natural resources by not damaging the environment and its main function. One of the utilization of environmental services is the utilization of water flow services and water utilization. Humans in their life processes use water for drinking, cooking, washing, and all other activities directly related to human welfare. This study aims to determine the factors that influence people's willingness to pay for environmental services, look for the value of Willingness To Pay (WTP), factors that influence the value of PAPs and the effect of the value of environmental service benefits on payments for environmental services. The willingness of respondents to make payments for environmental services is influenced by several factors, namely an assessment of the level of water quality, the amount of water needed in the household, and the average income in the household. This study aims to determine the factors that influence people's willingness to pay for environmental services, look for the value of willingness to pay (WTP), factors that influence the value of PAPs and influence the value of the benefits of environmental services on payments for the environment services. The willingness of respondents to make payments for environmental services is influenced by several factors, namely the assessment of the level of water quality, the amount of water needed in the household, and the average income in the household. The PAP value in this study is the value that will be given by respondents to the environmental services produced by the Lubuk Beringin Village Forest per cubic meter per household. The average value of PAPs for environmental improvement as water service services in the Lubuk Beringin Hamlet is Rp. 4,439, - / m3. The factors that influence the respondent's WTP value are influenced by the assessment of water quality level and average household income. The total value of PAPs from the population is Rp. 1,406,143 per month. The data shows that there are funds that can be used for 1 year of Rp. 16,873,716. The funds can be used to conserve the Village Forest area as an effort to maintain the environmental conditions of the Lubuk Beringin Village Forest as a provider of water use services by the community in the Lubuk Beringin Hamlet.